Isolated cleft sternum: Neonatal surgical treatment - Kanojia Ravi; Wakhlu Ashish; Wakhlu Avtar (Wolters Kluwer Medknow Publications, 2007)
Isolated cleft sternum is a rare congenital defect of the anterior chest wall and is the result of failed ventral midline fusion of sternal bands. We present two cases operated 18 and 24 days after birth with satisfactory results. Surgery is indicated to protect the heart and mediastinal contents.